Respuesta :

Answer:

Step-by-step explanation:

6) the answer is option b

y = - x + 3

x - y = 1

From the graph, the point at which the lines of the two equations meet is the solution to the system of equations

The points = x = 2 and y = 1

If you substitute these values in option b, it satisfies the equations.

7) the correct option is d

-x + y = -3 - - - - - - -1

2x -y = 6 - - - - - - 2

If we solve using elimination method,

Multiply equation 1 by 2 and equation 2 by 1

-2x + 2y = -6

2x -y = 6

Adding both equations

y = 0 and substituting y = 0 in equation 2,

x = 3

So y = 0 and x = 3

So it has only one solution

8) The lines of the two equations meet at a point where x = 3 and y = 0

Option d is the correct answer

-x +y = -3

2x - y = 6

Substituting x = 3 and y = 0 in option d,

- 3 + 0 = -3

6 - 0 = 6

9) y = x-2

x = 17-4y

Substituting y = x - 2 in x = 17 - 4y, we have

x = 17 -4(x - 2)

Opening the bracket

x = 17 - 4x + 8

x + 4x = 17 + 8

5x = 25

x = 25/5 = 5